Exposure to volatile organic compounds and chronic respiratory disease mortality, a case-cohort study - Mahdi Nalini; Hossein Poustchi; Deepak Bhandari; Benjamin C. Blount; Brandon M. Kenwood; Cindy M. Chang; Amy Gross; Christopher Ellison; Masoud Khoshnia; Akram Pourshams; Mitchell H. Gail; Barry I. Graubard; et al. (Respiratory Research)
Abstract Background Chronic respiratory diseases (CRDs) are the third leading cause of death worldwide. Data of the associations between specific volatile organic compounds (VOCs), a major component of air pollution and tobacco smoke, and subsequent CRD mortality in the general population are scarce. Methods In a case-cohort analysis within the population-based Golestan cohort study (n = 50045, aged 40–75 years, 58% women, enrollment: 2004–2008, northeastern Iran), we included all participants who died from CRD during follow-up through 2018 (n = 242) as cases and stratified them into 16 strata defined by age, sex, residence, and tobacco smoking. Subcohort participants (n = 610) were randomly selected from all eligible cohort participants in each stratum, and sampling fractions were calculated. Baseline urine samples were used to measure 20 VOCs using ultra high-performance liquid chromatography coupled with electrospray ionization tandem mass spectrometry. After excluding participants with previous history of CRDs, we used stratified Cox regression models weighted by the inverse sampling fractions (i.e. inverse probability weighting) adjusted for potential confounders, including urinary cotinine and pack-years of smoking, to calculate hazard ratios (HR) for the associations between biomarker tertiles and CRD mortality. Results Data from 545 non-case, sub-cohort participants and 149 cases (69.1% chronic obstructive pulmonary disease, 13.4% asthma, 17.5% other CRDs) were assessed in this study. During a follow-up of 10.5 years, associations [2nd and 3rd vs. 1st tertiles, HR (95% confidence interval), p for trend] were observed between metabolites of acrolein [1.56 (0.64,3.79), 3.53 (1.53,8.16), 0.002] and styrene/ethylbenzene [1.17 (0.53,2.60), 3.24 (1.37,7.66), 0.005] and CRD mortality, which persisted after excluding the first four years of follow-up. Conclusion Our findings support prior research suggesting respiratory toxicity of VOCs. Further investigation and monitoring of these compounds, especially acrolein and styrene/ethylbenzene, as CRD risk factors, are recommended.